(untitled) (Indian Journal of Public Health Research & Development, 2023)
Background: Pulmonary involvement is one of the most common extra-articular manifestation of rheumatoid arthritis (RA) and the second common cause of death due to infection. Pulmonary function tests are widely used to provide objective measure of lung function for detecting and quantifying pulmonary impairments. Material & Methods: This study was hospital based cross sectional nonintervention study. About 100 patients of rheumatoid arthritis have been selected from Rheumatology Clinic (OPD) of R. G. Kar Medical College and Hospital according to the ACR/EULAR diagnostic criteria, 2010. All patients were undergone for Hb% estimation, ESR determination, estimation of serum RA-factor, C-reactive protein and ACPA. Disease Activity of RA had determined by DAS-28 calculator. All cases and controls are undergone lung function test by means of electronic spirometer in the Department of Physiology of the same institute. Results: In our study 82% cases were female and 18% cases were males. In our study we got significant changes in lung function of the RA patients. FVC, FEV1, PEFR and FEF 25-75% etc. were significantly deteriorated, (p-value<0.0001). About 44% cases showed evidence of restrictive type of pulmonary function abnormality, it was significant (p-value<0.05) whereas only 2% cases show evidence of obstructive type of abnormality, which was not significant (p-value>0.05). There was definite correlation between disease duration and disease activity with abnormal pulmonary function, (p-value<0.0001). Conclusion: Therefore from the summary of this study, we can understand that lung function parameters can be used to stratify abnormalities in a clinically useful manner and lung function tests can be used as indicator of disease activity of rheumatoid arthritis. So all patients of RA should undergo PFTs to detect abnormality and by this way we can reduce morbidity and mortality of RA patients due to subclinical or overt pulmonary dysfunction.